Narrative Construction of the Free Nutritious Meals (MBG) Program on Social Media: A Framing Study of Supportive and Critical Content - Alwi Auvinen Juha; Dimas Affandi; Siti Rahma Lubis; Sherly Nurhaliza Br Damanik; Reviza Putra Syarif (Academic Solution Publisher, 2026)
This study aims to analyze the narrative construction of the Free Nutritious Meals Program (MBG) on social media through the framing constructed by supporters and critics. The study employed a qualitative method with a descriptive approach and Robert Entman's framing analysis model, which includes defining problems, diagnosing causes, making moral judgments, and recommending treatment. Data were obtained from comments, tweets, and social media posts discussing the MBG, which were then analyzed based on emerging themes and sentiments. The results show that supporters framed the MBG as a form of government social concern in addressing nutrition issues, improving child welfare, and encouraging community economic empowerment. Conversely, critics framed the MBG as a program still facing issues of implementation, food quality, benefit distribution, and the effectiveness of state budget use. These differences in framing are evident through the use of language, symbols, and emotions that shape the direction of public opinion. The research findings indicate that social media functions as an arena for shaping reality and public opinion through a framing process that generates both legitimacy and criticism of government policies. Thus, the construction of the MBG narrative on social media reflects a contestation of meaning that influences public perception of public policy in the digital communication era.